1991
DOI: 10.1111/j.1471-4159.1991.tb08177.x
|View full text |Cite
|
Sign up to set email alerts
|

[3H]Harman Binding Experiments. I: A Reversible and Selective Radioligand for Monoamine Oxidase Subtype A in the CNS of the Rat

Abstract: Harman (1-methyl-beta-carboline) is an endogenous compound with neurotropic properties in rats and humans. In a novel in vitro binding assay, the binding site of [3H]harman has been characterized in the rat crude mitochondrial (P2) fraction. The binding was saturable and reversible. Only a single high-affinity binding site was detected by kinetic, saturation, and displacement analyses in the cerebral cortex of the rat. The linear Scatchard plots revealed equilibrium dissociation constant (KD) values of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 40 publications
(41 reference statements)
2
29
0
1
Order By: Relevance
“…Norharman inhibits preferentially MAO-B (May et al, 1991) and is found in substantia nigra from humans (Matsubara et al, 1993). The plasma levels of harman and norharman are also increased in parkinsonian patients (Kuhn et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norharman inhibits preferentially MAO-B (May et al, 1991) and is found in substantia nigra from humans (Matsubara et al, 1993). The plasma levels of harman and norharman are also increased in parkinsonian patients (Kuhn et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Harman, a 1-methylated derivative of norharman, has been reported to have a strong inhibitory action of monoamine oxidase type A (MAO-A, EC 1.4.3.4) (May et al, 1991). Norharman inhibits preferentially MAO-B (May et al, 1991) and is found in substantia nigra from humans (Matsubara et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown that acetaldehyde and nicotine when applied together exhibited synergistic positive reinforcing effects in self-administering rats (152). It was further speculated that, by reacting with certain aromatic amines, acetaldehyde may give rise to β-carbolines -a group of compounds possibly inhibiting the activity of monoamino oxidase (430,431). With these notions in mind it was assumed that acetaldehyde generated from sugars might enhance nicotine addictiveness (92,429).…”
Section: Sugarsmentioning
confidence: 99%
“…rice, wheat, barley, rye, corn, soybeans, mushrooms, grapes, vinegar, wine and beer. These alkaloids are considered to possess pharmacological properties related to the central nervous system -tremorogenesis (12), hypothermia (1), hallucinogenesis (8) and monoamine oxidase inhibition (13,15). In experimental animals (guinea-pigs), harmane, harmine and harmaline have also been demonstrated to cause spasmolytic effects on isolated trachea (17).…”
Section: Introductionmentioning
confidence: 99%